Anti-caries additives, anti-caries materials, dental films and invisible orthodontic appliances
By introducing hydrotalcite and fluoride ion inserts of carbonate inserts into the materials of the invisible remedies, an additive with anti-calcification effect was formed, which solved the problem of the lack of anti-calcification of existing invisible remediation devices, and achieved stable and long-lasting anti-calcification of dental caries. Effect.
Patent Information
- Application Number
- CN202310176448.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The existing invisible remedies lack the effect of preventing dental caries, which makes it easy to cause dental caries, periodontal disease and other oral diseases when worn.
A dental caries-proof additive is adopted. This additive is used to prepare hydrotalcite like carbonate intercalation and add fluoride ion intercalation to form a bimetallic hydroxide and fluoride aqueous solution. After calcination and heating treatment, it can obtain anti-static Materials for dental caries effect. This material is used to prepare dental diaphragms and invisible remedies.
By introducing fluoride ion intercalation hydrotalcite, the material can release fluoride ions, promote the formation of apatite in the hard tissue of the tooth, reduce the solubility of enamel, inhibit the fermentation and acid production of caries-causing bacteria, thereby achieving stable and long-lasting dental prevention Effect.
Smart Images

Figure BDA0004101011380000211 
Figure BDA0004101011380000221
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to an anti-caries additive, an anti-caries material, a dental film and an invisible orthodontic appliance. Background Art
[0002] Invisible braces are gradually replacing traditional bracket braces and becoming the mainstream. The main materials of invisible braces are PET, PETG and TPU. The change of brace membrane material can provide longer-lasting correction force and more comfort. However, wearing invisible braces still has a certain impact on the oral environment, which can easily cause oral diseases such as tooth decay, periodontal disease, and pulp disease. At present, few invisible braces on the market have the effect of preventing and treating tooth decay. Summary of the invention
[0003] The present invention is made to solve the above-mentioned problems, and aims to provide an anti-caries additive, an anti-caries material, a dental film and an invisible orthodontic appliance with stable and lasting anti-caries effect.
[0004] The present invention provides an anti-caries additive, characterized in that the anti-caries additive is prepared by the following method:
[0005] Step 1, prepare a general structural formula [M II (1-x) M III x (OH)2] x+ (CO3 2- ) x / 2 ·mH2O carbonate intercalated hydrotalcite, of which 0.2 <x<0.33,M II represents a divalent metal ion, M III The preparation method of hydrotalcite-like carbonate intercalated layers representing trivalent metal ions is as follows:
[0006] Step 1-1, dissolving a divalent metal ion salt and a trivalent metal ion salt in water to form a clear and transparent mixed salt solution,
[0007] Step 1-2, dissolving carbonate and hydroxide in water to form a clear and transparent mixed alkaline solution,
[0008] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2, stirring continuously during the dropping process to obtain a suspension, heating the suspension, and performing a hydrothermal reaction at a constant temperature. After the reaction is completed, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite-like substance,
[0009] The amount of the added divalent metal ion salt, trivalent metal ion salt, carbonate, and hydroxide is determined according to the general structural formula of the carbonate intercalated hydrotalcite.II 、M III OH - and CO3 2- The atomic number ratio of (1-x): x: 2: x / 2 is added;
[0010] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 to obtain a double metal hydroxide;
[0011] Step 3, adding the double metal hydroxide prepared in step 2 to a fluoride aqueous solution, heating and stirring under the protection of an inert gas, filtering, washing, drying and crushing after the reaction to obtain a fluoride ion intercalated hydrotalcite.
[0012] Furthermore, in the anti-caries additive provided by the present invention, it may also have the following characteristics: the carbonate is sodium carbonate or potassium carbonate;
[0013] The hydroxide is sodium hydroxide or sodium potassium hydroxide;
[0014] The divalent metal ion is any one of magnesium ion, calcium ion, barium ion, copper ion, zinc ion and ferrous ion;
[0015] The trivalent metal ion is any one of iron ion, aluminum ion, cobalt ion and cerium ion;
[0016] The fluoride is any one of sodium fluoride, potassium fluoride and ammonium fluoride.
[0017] Furthermore, the anti-caries additive provided by the present invention may also have the following characteristics: in steps 1-3, the temperature of the mixed salt solution when it is added dropwise to the mixed alkali solution is 20°C-60°C, the suspension is heated to 100°C-160°C for hydrothermal reaction, and the hydrothermal reaction time is 6h-48h.
[0018] Furthermore, the anti-caries additive provided by the present invention may also have the following feature: the calcination temperature in step 2 is 400°C-700°C.
[0019] Furthermore, the anti-caries additive provided by the present invention may also have the following characteristics: the reaction temperature in step 3 is 50°C-100°C, the reaction time is 12h-24h, and the ratio of the molar mass of fluoride in the fluoride aqueous solution to the molar mass of carbonate in step 1-2 is (2±0.2): 1. The fluoride concentration is not limited as long as it is a clear and transparent solution.
[0020] The present invention also provides an anti-dental caries material, characterized in that the anti-dental caries material is prepared by using TPU and the above-mentioned anti-dental caries additive.
[0021] Furthermore, the anti-caries material provided by the present invention may also have the following characteristics: the preparation method of the anti-caries material is:
[0022] Step 1, putting the TPU resin into an oven, heating it to 70-90°C, and drying it for 4-8h to obtain a dry TPU resin;
[0023] Step 2, placing the anti-caries additive according to claim 6 into an oven, heating it to 180-250° C., and drying it for 12-24 hours to obtain a dry anti-caries additive;
[0024] Step 3, adding dry TPU resin and dry anti-caries additive into a stirrer, stirring evenly, discharging, adding into a twin-screw extruder, and performing melt extrusion granulation to obtain an anti-caries material. Specifically, the TPU resin and the anti-caries additive are set according to the required fluoride ion content.
[0025] The present invention also provides a dental membrane, characterized in that the dental membrane is prepared by using the above-mentioned anti-caries material.
[0026] The present invention also provides an invisible brace appliance, characterized in that the invisible brace appliance is prepared by using the above-mentioned dental film.
[0027] The present invention has the following advantages:
[0028] The anti-caries material of the present invention introduces fluorine ion intercalated hydrotalcite into the TPU membrane so that the membrane has a certain anti-caries effect. Since the fluorine ion intercalated hydrotalcite is not stable, it is easy to be replaced by other ions in the environment, thereby releasing a certain amount of fluorine ions. A small amount of fluoride can accelerate the formation of apatite in the hard tissue of the tooth and increase its stability; fluorine can reduce the solubility of enamel, promote the remineralization of enamel, form deposition in the demineralized area, and promote the repair and reconstruction of caries lesions; fluorine can inhibit the fermentation and acid production of cariogenic bacteria and reduce the corrosion of tooth tissue, thereby preventing the occurrence of caries. In addition, due to the slow release of fluorine ions released by hydrotalcite, by adjusting the content of fluorine ion intercalated hydrotalcite in the anti-caries material, the fluorine content in the anti-caries material is easy to control, which can ensure human health and safety.
[0029] The dental film of the present invention is prepared by anti-caries material and therefore has a stable and lasting anti-caries effect.
[0030] The invisible orthodontic appliance of the present invention is prepared by using the dental film of the present invention, and therefore has a stable and lasting anti-caries effect. DETAILED DESCRIPTION
[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following examples specifically describe the anti-caries additive, anti-caries material, dental film and invisible braces of the present invention.
[0032] Example 1
[0033] The anti-caries additive is prepared by the following method:
[0034] Step 1, prepare the structural formula Mg 0.8 Al 0.2 (OH)2(CO3) 0.1 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.8:0.2:2:0.1 for adding materials.
[0035] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0036] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0037] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0038] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 500° C. to obtain a double metal hydroxide;
[0039] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a1.
[0040] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0041] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0042] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0043] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0044] The anti-caries material is prepared into a dental film.
[0045] The above dental film is used to prepare invisible braces.
[0046] Example 2
[0047] The anti-caries additive is prepared by the following method:
[0048] Step 1, prepare the structural formula Mg 0.75 Al 0.25 (OH)2(CO3) 0.125 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.75:0.25:2:0.125 for adding material.
[0049] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0050] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0051] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0052] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 500° C. to obtain a double metal hydroxide;
[0053] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a2.
[0054] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0055] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0056] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0057] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0058] The anti-caries material is prepared into a dental film.
[0059] The above dental film is used to prepare invisible braces.
[0060] Example 3
[0061] The anti-caries additive is prepared by the following method:
[0062] Step 1, prepare the structural formula Mg 0.67 Al 0.33 (OH)2(CO3) 0.165 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.67:0.33:2:0.165 for adding material.
[0063] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0064] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0065] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0066] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 500° C. to obtain a double metal hydroxide;
[0067] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a3.
[0068] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0069] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0070] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0071] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0072] The anti-caries material is prepared into a dental film.
[0073] The above dental film is used to prepare invisible braces.
[0074] Example 4
[0075] The anti-caries additive is prepared by the following method:
[0076] Step 1, prepare the structural formula Mg 0.7 Al 0.3 (OH)2(CO3) 0.15 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, carbonate ions in potassium carbonate, and hydroxide ions in potassium hydroxide is Mg: 2+ :Al 3+ :OH- :CO3 2- =0.7:0.3:2:0.15 for adding material.
[0077] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0078] Step 1-2, dissolving sodium carbonate and sodium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0079] Step 1-3, adding the mixed salt solution prepared in step 1-1 to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 150° C., performing a hydrothermal reaction at a constant temperature, reacting for 24 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0080] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 600° C. to obtain a double metal hydroxide;
[0081] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of sodium carbonate in step 1-2, heating to 80° C. with stirring under the protection of an inert gas, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a4.
[0082] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0083] Step 1, putting the TPU resin into an oven, heating it to 90° C., and drying it for 4 hours to obtain a dry TPU resin;
[0084] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0085] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0086] The anti-caries material is prepared into a dental film.
[0087] The above dental film is used to prepare invisible braces.
[0088] Example 5
[0089] The anti-caries additive is prepared by the following method:
[0090] Step 1, prepare the structural formula Mg 0.7 Al 0.3 (OH)2(CO3) 0.15 The molar ratio of magnesium ions in magnesium chloride hexahydrate, chloride ions in aluminum nitrate nonahydrate, carbonate ions in potassium carbonate, and hydroxide ions in potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.7:0.3:2:0.15 for adding material.
[0091] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0092] Step 1-2, dissolving sodium carbonate and sodium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0093] Step 1-3, adding the mixed salt solution prepared in step 1-1 to the mixed alkali solution prepared in step 1-2 at a temperature of 20° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 100° C., and performing a hydrothermal reaction at a constant temperature. After reacting for 24 hours, the carbonate-intercalated hydrotalcite is obtained after filtering, washing, drying, and crushing.
[0094] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 700° C. to obtain a double metal hydroxide;
[0095] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of 2% potassium fluoride aqueous solution, wherein the molar mass of fluoride ions in the potassium fluoride aqueous solution is equal to twice the molar mass of sodium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a5.
[0096] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0097] Step 1, putting the TPU resin into an oven, heating it to 90° C., and drying it for 6 hours to obtain a dry TPU resin;
[0098] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 220° C., and drying for 18 hours to obtain a dry anti-caries additive;
[0099] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0100] The anti-caries material is prepared into a dental film.
[0101] The above dental film is used to prepare invisible braces.
[0102] Example 6
[0103] The anti-caries additive is prepared by the following method:
[0104] Step 1, prepare Zn 0.7 Al 0.3 (OH)2(CO3) 0.15 The molar ratio of zinc ion in zinc chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate and sodium hydroxide is: Zn 2+ :Al 3+ :OH - :CO3 2- =0.7:0.3:2:0.15 for adding material.
[0105] Step 1-1, dissolving zinc chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0106] Step 1-2, dissolving sodium carbonate and sodium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0107] Step 1-3, adding the mixed salt solution prepared in step 1-1 to the mixed alkali solution prepared in step 1-2 at a temperature of 60° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 100° C., performing a hydrothermal reaction at a constant temperature, reacting for 24 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0108] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 700° C. to obtain a double metal hydroxide;
[0109] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of 2% potassium fluoride aqueous solution, wherein the molar mass of fluoride ions in the potassium fluoride aqueous solution is equal to twice the molar mass of sodium carbonate in step 1-2, heating to 50° C. under the protection of an inert gas with stirring, reacting for 24 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a6.
[0110] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0111] Step 1, putting the TPU resin into an oven, heating it to 80° C., and drying it for 6 hours to obtain a dry TPU resin;
[0112] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 180° C., and drying for 24 hours to obtain a dry anti-caries additive;
[0113] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0114] The anti-caries material is prepared into a dental film.
[0115] The above dental film is used to prepare invisible braces.
[0116] Example 7
[0117] The anti-caries additive is prepared by the following method:
[0118] Step 1, prepare a Cu 0.7 Fe 0.3 (OH)2(CO3) 0.15 The molar ratio of copper ions in copper chloride dihydrate, iron nitrate nonahydrate, carbonate ions in potassium carbonate, and hydroxide ions in sodium hydroxide is Cu: 2+ :Fe 3+ :OH - :CO3 2- =0.7:0.3:2:0.15 for adding material.
[0119] Step 1-1, dissolving cupric chloride dihydrate and ferric nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0120] Step 1-2, dissolving sodium carbonate and sodium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0121] Step 1-3, adding the mixed salt solution prepared in step 1-1 to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 100° C., and performing a hydrothermal reaction at a constant temperature. After reacting for 24 hours, the carbonate-intercalated hydrotalcite is obtained after filtering, washing, drying, and crushing.
[0122] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 700° C. to obtain a double metal hydroxide;
[0123] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of sodium carbonate in step 1-2, heating to 100° C. under the protection of an inert gas and stirring, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a7.
[0124] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0125] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 8 hours to obtain a dry TPU resin;
[0126] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 250° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0127] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0128] The anti-caries material is prepared into a dental film.
[0129] The above dental film is used to prepare invisible braces.
[0130] Comparative Example 1
[0131] The anti-caries additive is prepared by the following method:
[0132] Step 1, prepare the structural formula Mg 0.8 Al 0.2 (OH)2(CO3) 0.1 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.8:0.2:2:0.1 for adding materials.
[0133] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0134] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0135] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0136] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 400° C. to obtain a double metal hydroxide;
[0137] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. with stirring under the protection of an inert gas, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a8.
[0138] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0139] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0140] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0141] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0142] The anti-caries material is prepared into a dental film.
[0143] The above dental film is used to prepare invisible braces.
[0144] Comparative Example 2
[0145] The anti-caries additive is prepared by the following method:
[0146] Step 1, prepare the structural formula Mg 0.75 Al 0.25 (OH)2(CO3) 0.125The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.75:0.25:2:0.125 for adding material.
[0147] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0148] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0149] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0150] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 800° C. to obtain a double metal hydroxide;
[0151] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a9.
[0152] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0153] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0154] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 200° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0155] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0156] The anti-caries material is prepared into a dental film.
[0157] The above dental film is used to prepare invisible braces.
[0158] Comparative Example 3
[0159] The anti-caries additive is prepared by the following method:
[0160] Step 1, prepare the structural formula Mg 0.67 Al 0.33 (OH)2(CO3) 0.165 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, potassium carbonate, and potassium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.67:0.33:2:0.165 for adding material.
[0161] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0162] Step 1-2, dissolving potassium carbonate and potassium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0163] Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 120° C., performing a hydrothermal reaction at a constant temperature, reacting for 12 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0164] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 500° C. to obtain a double metal hydroxide;
[0165] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of potassium carbonate in step 1-2, heating to 80° C. under the protection of an inert gas with stirring, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a10.
[0166] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0167] Step 1, putting the TPU resin into an oven, heating it to 70° C., and drying it for 4 hours to obtain a dry TPU resin;
[0168] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to 150° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0169] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0170] The anti-caries material is prepared into a dental film.
[0171] The above dental film is used to prepare invisible braces.
[0172] Comparative Example 4
[0173] The anti-caries additive is prepared by the following method:
[0174] Step 1, prepare the structural formula Mg 0.7 Al 0.3 (OH)2(CO3) 0.15 The molar ratio of magnesium ions in magnesium chloride hexahydrate, aluminum nitrate nonahydrate, carbonate ions in potassium carbonate, and hydroxide ions in sodium hydroxide is Mg: 2+ :Al 3+ :OH - :CO3 2- =0.7:0.3:2:0.15 for adding material.
[0175] Step 1-1, dissolving magnesium chloride hexahydrate and aluminum nitrate nonahydrate in water to form a clear and transparent mixed salt solution.
[0176] Step 1-2, dissolving sodium carbonate and sodium hydroxide in water to form a clear and transparent mixed alkaline solution.
[0177] Step 1-3, adding the mixed salt solution prepared in step 1-1 to the mixed alkali solution prepared in step 1-2 at a temperature of 30° C., stirring continuously during the dropping process to obtain a suspension, heating the suspension to 150° C., performing a hydrothermal reaction at a constant temperature, reacting for 24 hours, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite.
[0178] Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 at 600° C. to obtain a double metal hydroxide;
[0179] Step 3, adding the double metal hydroxide prepared in step 2 to an appropriate amount of sodium fluoride aqueous solution with a mass fraction of 2%, wherein the molar mass of fluoride ions in the sodium fluoride aqueous solution is equal to twice the molar mass of sodium carbonate in step 1-2, heating to 80° C. with stirring under the protection of an inert gas, reacting for 20 hours, filtering, washing, drying, and crushing to obtain a fluoride ion intercalated hydrotalcite, the product being recorded as a4.
[0180] An anti-caries material containing 20% of an anti-caries additive is prepared. The preparation process is as follows:
[0181] Step 1, putting the TPU resin into an oven, heating it to 90° C., and drying it for 4 hours to obtain a dry TPU resin;
[0182] Step 2, putting the above-mentioned anti-caries additive into an oven, the added amount is one quarter of the amount of TPU resin added in step 1, heating to d300° C., and drying for 12 hours to obtain a dry anti-caries additive;
[0183] Step 3, adding the dry TPU resin and the dry anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain the anti-caries material.
[0184] The anti-caries material is prepared into a dental film.
[0185] The above dental film is used to prepare invisible braces.
[0186] 1 g of each dental film in Examples 1-7 and Comparative Examples 1-4 was taken and immersed in 1 L of oral simulated liquid environment. After one week, an appropriate amount of liquid was taken and the change of fluoride ion concentration in the environment after release was tested by ion chromatography. The film state and fluoride ion concentration in each example are shown in Table 1.
[0187] Table 1
[0188]
[0189]
[0190] As can be seen from Examples 1-7, Comparative Example 1 and Comparative Example 2 in Table 1, the calcination temperature has a great influence on the release effect of the anti-caries additive: as can be seen from Comparative Example 1 and Comparative Example 2, when the calcination temperature is 400 °C, the fluoride ion concentration drops significantly. Since the carbonate radicals do not escape completely due to the too low temperature, it is not conducive to the reorganization of the fluoride ion intercalated hydrotalcite; when the calcination temperature is 800 °C, the fluoride ion concentration also drops significantly. Since the double metal oxide is sintered, it is also not conducive to the reorganization of the fluoride ion intercalated hydrotalcite. According to the required fluoride ion concentration, the optimal calcination temperature is determined to be 400 °C - 700 °C. As can be seen from Examples 1-3, the structure of the carbonate intercalated hydrotalcite-like material also has a certain influence on the fluoride ion release. In the structural general formula II (1-x) M III x (OH)2] x+ (CO3 2- ) x / 2 ·mH2O (0.2 < x < 0.33), when other conditions are the same, as the value of x increases, the released fluoride ion concentration decreases. When preparing the anti-caries material, as can be seen from Comparative Example 3, when the drying temperature of the anti-caries additive is too low, bubbles will appear in the processed dental film; as can be seen from Example 4 and Comparative Example 4, when the drying temperature of the anti-caries additive is too high, it will also affect the fluoride ion concentration. Therefore, when preparing the anti-caries material, an appropriate drying temperature is required to remove the crystal water in the hydrotalcite, otherwise it may affect the film processing.
[0191] The anti-caries additive, anti-caries material, dental film and invisible orthodontic appliance involved in the present invention are not limited to the scope of the specific embodiments. The above content is only the basic description of the present invention, and any equivalent transformation based on the technical solution of the present invention shall fall within the protection scope of the present invention.
Claims
1. An anti-caries material, characterized in that: The anti-caries material is prepared by using TPU and an anti-caries additive, and the preparation method of the anti-caries material is as follows: Step 1, putting the TPU resin into an oven, heating it to 70°C-90°C, and drying it for 4-8 hours to obtain a dry TPU resin; Step 2, placing the anti-caries additive in an oven, heating it to 180° C.-250° C., and drying it for 12 h-24 h to obtain a dry anti-caries additive; Step 3, adding the dried TPU resin and the dried anti-caries additive into a stirrer, stirring evenly, discharging the mixture, adding the mixture into a twin-screw extruder, and subjecting the mixture to melt extrusion and granulation to obtain an anti-caries material; Wherein, the anti-caries additive is prepared by the following method: Step 1, prepare a general structural formula [M II (1-x) M III x (OH)2] x+ (CO3 2- ) x / 2 ·mH2O carbonate intercalated hydrotalcite, of which 0.2 <x<0.33,M II represents a divalent metal ion, M III The preparation method of hydrotalcite-like materials with carbonate intercalation representing trivalent metal ions is as follows: Step 1-1, dissolving a divalent metal ion salt and a trivalent metal ion salt in water to form a clear and transparent mixed salt solution, Step 1-2, dissolving carbonate and hydroxide in water to form a clear and transparent mixed alkaline solution, Step 1-3, adding the mixed salt solution prepared in step 1-1 dropwise to the mixed alkali solution prepared in step 1-2, stirring continuously during the dropping process to obtain a suspension, heating the suspension, and performing a hydrothermal reaction at a constant temperature. After the reaction is completed, filtering, washing, drying, and crushing to obtain a carbonate-intercalated hydrotalcite-like substance, The amount of the added divalent metal ion salt, trivalent metal ion salt, carbonate, and hydroxide is determined according to the general structural formula of the carbonate intercalated hydrotalcite. II 、M III OH - and CO3 2- The atomic number ratio of (1-x): x: 2: x / 2 is added; Step 2, calcining the carbonate-intercalated hydrotalcite prepared in step 1 to obtain a double metal hydroxide, wherein the calcination temperature is 500° C.-700° C.; Step 3, adding the double metal hydroxide prepared in step 2 to a fluoride aqueous solution, heating and stirring under the protection of an inert gas, filtering, washing, drying and crushing after the reaction to obtain a fluoride ion intercalated hydrotalcite.
2. The anti-caries material according to claim 1, characterized in that: The carbonate is sodium carbonate or potassium carbonate; The hydroxide is sodium hydroxide or sodium potassium hydroxide; The divalent metal ion is any one of magnesium ion, calcium ion, barium ion, copper ion, zinc ion and ferrous ion; The trivalent metal ion is any one of iron ion, aluminum ion, cobalt ion and cerium ion; The fluoride is any one of sodium fluoride, potassium fluoride and ammonium fluoride.
3. The anti-caries material according to claim 1, characterized in that: In step 1-3, the temperature of the mixed salt solution when it is added dropwise to the mixed alkali solution is 20°C-60°C, and the suspension is heated to 100°C-160°C for hydrothermal reaction, and the hydrothermal reaction time is 6h-48h.
4. The anti-caries material according to claim 1, characterized in that: The reaction temperature in step 3 is 50° C.-100° C., the reaction time is 12 h-24 h, and the ratio of the molar mass of fluoride in the fluoride aqueous solution to the molar mass of carbonate in step 1-2 is (2±0.2):
1.
5. A dental film, characterized in that: The dental film is prepared by using the anti-caries material according to any one of claims 1 to 4.
6. A dental invisible orthodontic appliance, characterized in that: The invisible tooth brace is prepared using the dental film according to claim 5.
Citation Information
Patent Citations
Ibuprofen intercalated magnesium-aluminum hydrotalcite sustained-release material and preparation method thereof
CN111744017A
Use of a solid hydrotalcite structure incorporating fluorides for basic catalysis of michael or knoevenagel reactions
US20030166462A1
Dental cleaning composition and method
US4296094A
Fluorine containing dental materials
WO1982004259A1